An assessment of entrepreneurial intention among postgraduate students in Nigerian Universities - Idrisu, Adamu Abdullahi (2015)
Governments in most developing countries are doing their best to ensure that graduates who are not employed should engage in entrepreneurship activities which can go a long way in reducing the problem of unemployment among the youths. Nigeria is among one of those developing nations with such problem. The government has introduced some many programmes and policies which are aimed at reducing poverty and will encourage self-employment among the youths. Yet, students are still lacking the intention of becoming an entrepreneur. Thus, this study aimed in examining the entrepreneurial intention among postgraduate students in Nigerian universities. The study used factors such as entrepreneurship education, environmental factors and societal entrepreneurship attitude to explore the student's entrepreneurial intention. Also, the study used a convenient sampling method with 254 questionnaires were administered to three universities. The result indicated that all the independent variables used (entrepreneurship education, environment factors and societal entrepreneurship attitude) has positive significant and are related to entrepreneurial intention. Finally, this study finding is important to the Ministry of Education on how to design a more comprehensive and benefice entrepreneurship courses and curriculum to these Nigerian universities. This will aim at preparing these students to be self-employed (entrepreneurs) which will reduce and assist the government in overcoming the problem of youth poverty and unemployment in Nigeria